FORMULATION DEVELOPMENT AND EVALUATION OF TOPICAL DRUG DELIVERY SYSTEM - Dr. Shashikant D. Barhate; Dr. Sandip R. Pawar (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Topical delivery has been developed for variety of disease and disorders. The treatment of skin diseases additionally as musculoskeletal disorders may well be advantageous from topical administration obtaining a substantial reduction in oral side effects with improved patient compliance. Many anti-inflammatory drugs are poorly water soluble and Nano suspension is that the techniques which is employed to enhance this characteristic, so anti-inflammatory drugs are chosen as a model for this study. Rizatriptan is employed to treat migraines. It helps to alleviate headache, pain, and other migraine symptoms (including nausea, vomiting, and sensitivity to light/sound). Prompt treatment helps you come back to your normal routine and should decrease your need for other pain medications. Rizatriptan belongs to a category of medicine called triptans. It affects a specific natural substance (serotonin) that causes narrowing of blood vessels within the brain. It’s going to also relieve ache by affecting certain nerves inside the brain. Rizatriptan don't prevent future migraines or lessen how often you get migraine attacks the improved adoption of topical medication in current years has been impressive. this can be largely thanks to the very fact that the medication has proven to own more advantages than drawbacks. After all, the skin is right for drug administration, because it produces both systematic and native effects. Call it a life-changing medical innovation. Topical drug delivery systems have surely changed the way we glance at medication. More and more medical institutions and health practitioners are adopting this kind of medication in an endeavor to boost their services to patients.